Desain Pembelajaran Kooperatif Learning Teknik Kancing Gemerincing pada Bahasa Indonesia Kelas V - Agus Suryana; Della Assyifa Nur Aqilah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
The writing of this article aims to: Explain the Design of Cooperative Learning Learning the Rattlesnake Technique in Indonesian Class V Interview Materials, Explaining the Advantages of Cooperative Learning Designs for Learning the Clinking Button Techniques in Indonesian Class V Interview Materials, This research method uses the library method by analyzing various books and journals related to Cooperative Learning Design Learning jingling button technique in Indonesian Class V Interview Material. The conclusions concluded that: The rattling button technique learning model is a learning model that has clear and systematic procedures, the rattling button learning model was originally developed by spancer Kagan in 1990. Another advantage of this jingling button technique is that students' attention can be focused, overcoming obstacles Equity distribution which is often dominated by certain students, can stimulate students to be more active and can answer all the problems that arise in the minds of each student because they take part directly, and equal distribution of responsibilities can be achieved, no member depends on his dominant partner. The steps of the cooperative learning model of the rattling button technique are (1) The teacher prepares a small box containing buttons (can also be other small objects, such as red beans, hazelnut seeds, pieces of straw, sticks, scoop of ice cream). , etc). These buttons can also be replaced with other objects, (2) Before the group starts their task, each student in each group gets two or three buttons (the number of buttons depends on the difficulty of the task given), (3) Each time a child If a child is to speak or express an opinion, he must throw away one of his buttons and put it in the middle, (4) If a child's buttons run out, he may not speak again until all his friends have also finished their buttons, (5) If all the buttons have been finished, while the task has not been completed, the group may take an agreement to divide the buttons again and repeat the procedure again. Keywords: Kancing Gemerincing, Cooperative Learning Model Design, Indonesian Language Learning